An Investigation of the Effects of Different Warm-Up Protocols on Some Performance Values of Young Football Players - Mihri Barış KARAVELİOĞLU; Serkan Hüsnü KORKMAZ; Gökhan HADİ; Serkan AYDIN (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
The aim of this study is to investigate the effects of different warm-up protocols on some performance values of young football players. A total of 23 young football players with an age, height and body weight mean of 11,46±0,58 years, 151,73±6,69 cm and 41,47±6,83 kg, respectively, participated in the study voluntarily. Three different warm up protocols were applied to the participants, 48 hours apart. These different warm-up protocols were designed as; a 10 minute-warm-up run (Method A), a dynamic + static warm-up (Method B) and a static + dynamic warm-up (Method C). 30 m. speed, agility, dribbling and ball juggling performance values of the participants were measured after each warm-up. The data was analysed using IBM SPSS 26 package programme. One-way analysis of variance (ANOVA) was used for intergroup comparisons, and Tukey HSD test was used for Post Hoc comparisons of significant relationships. Significance level was accepted as p<0.05. As a result, it has been determined that the static + dynamic warm-up protocol has a positive effect on the dribbling and juggling performances of football players compared to the warm-up run and dynamic + static warm-up protocols.